Countering the Spread of LGBTQ+ in Post Covid-19 Era - Aulia Putri Meidina; Siti Nur Laili Rahmawati (Universitas Darussalam Gontor, 2023)
The LGBTQ+ phenomenon has been increasingly spreading in society lately, especially on social media, where campaigns and support for the normalization of this phenomenon are easily found, even among the majority Muslim population in Indonesia. However, based on Islamic teachings, such behavior is considered deviant and should be condemned. One of the efforts to contain the spread of this phenomenon is carried out by the Instagram account @taulebih.id, an Islamic sexuality education platform. This research aims to understand the message packaging strategies in the content uploaded by @taulebih.id. The research utilizes Phillip Mayring’s qualitative content analysis method, based on the Tarbiyah Jinsiyah theory proposed by Nasih Ulwan. During the month of June 2022, @taulebih uploaded content related to countering LGBT+ in various forms, including single posts, carousel posts, and reel videos with anti-LGBTQ+ topics. The messages are presented in the form of comics, depicting snippets of daily interactions within families and classrooms. The language used is adapted to everyday usage. Each content also includes references such as journals, books, or articles to strengthen the credibility of the conveyed message. In general, @taulebih takes a stance against LGBTQ+ by delivering firm messages, yet in a friendly manner, and making efforts to embrace those who are perceived as deviating.